"Click" polymerization: a convenient strategy to prepare designer fullerene materials - Krishnamurthy, Munusamy; Krishnamoorthy, Kothandam; Arulkashmir, Arulraj; Raghavendra, V.; Murali, Adhigan; Jaisankar, Sellamuthu N.; Murugan, P.; Gurusamy-Thangavelu, Senthil A.; Nasar, A. Sultan; Mandal, Asit Baran; Samanta, Debasis (Materials & Design, 2016)
"Click" polymeric assemblies of fullerenes, thiophenes and aryl compounds were prepared for the first time to study their spectroscopic/chemical/electronic characteristics and possible applications in photovoltaic cells. The GPC and NMR spectroscopic data confirmed a moderate to high degree of polymerization while microscopic pictures showed well-defined arrangements of fullerenes. The FTIR studies indicated that the product is free from starting azide materials, whereas thermogravimetric analysis data suggested a good stability. Band gap of the material was determined using UV-Vis spectroscopy, cyclic voltammetric techniques and compared with computational investigation. The fullerene copolymer was fabricated as acceptor material in a bulk heterojunction photovoltaic cell. (C) 2016 Elsevier Ltd. All rights reserved.

Experimental and theoretical investigations of different diketopyrrolopyrrole-based polymers - Murugan, Pachaiyappan; Raghavendra, Venkatraman.; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Mandal, Asit Baran; Subramanian, Venkatesan; Samanta, Debasis (ACS Omega, 2018)
Diketopyrrolopyrrole (DPP)-based polymers are often considered las the most promising donor moiety in traditional bulk heterojunction solar cell devices. In this paper, we report the synthesis, characterization of various DPP-based copolymers with different molecular weights, l and polydisper sity where other aromatic repeating units (phenyl or thiophene based) are connected by alternate double bonds or triple bonds. Some of the copolymers were used for device fabrication and the crucial parameters such as fill factor (FF) and open circuit voltage (V-oc) were calculated. The density functional theory was used to optimize the geometries and deduce highest occupied molecular orbital lowest unoccupied molecular orbital gaps of all the polymers and'theoretically predict their optical and electronic properties. Optical properties of all the polymers, electrochemical properties and band gaps were also obtained experimentally and compared with the theoretically predicted values.